Social Media Communication and Cultural Adaptation among University Students in Padang City - Elfemi, Nilda; Dikchanio, Farren Tri; Azizah, Nurul; Ramadhan, Satria; Pratama, Sultan Dika; Andria, Vibra Munzilla (Journal of Humanity Studies, 2025)
This study examines the role of social media in intercultural communication and cultural adaptation among university students in Padang City. The increasing diversity of student backgrounds has intensified interactions across cultural and linguistic boundaries, particularly within digital communication spaces. Using a qualitative approach with a descriptive case study design, this research explores how migrant and local students communicate, adapt, and manage cultural differences through social media platforms. Data were collected through in-depth interviews, participant observation, and analysis of online interactions involving university students from various academic institutions in Padang.